2013
DOI: 10.1162/rest_a_00292
|View full text |Cite
|
Sign up to set email alerts
|

Do Natural Resources Attract Nonresource FDI?

Abstract: A new and extensive panel of outward nonresource and resource FDI is used to investigate the effect of natural resources on the different components of FDI. Our main findings are as follows. First, for countries which were not a resource producer before, a resource discovery causes nonresource FDI to fall 16% in the short run and by 68% in the long run. Second, for countries that were already a resource producer, a doubling of resource rents induces a 12.4% fall in nonresource FDI. Third, on average, the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 58 publications
(46 reference statements)
4
57
1
1
Order By: Relevance
“…These results are further explained in Poelhekke and van der Ploeg (2013) with the same sample in the same period. They reported that in previously non-resource countries, discovering resources led to nonresource FDI to decreasing by 16% in the short term and by 68% in the long term.…”
Section: Review Of Literaturesupporting
confidence: 54%
See 1 more Smart Citation
“…These results are further explained in Poelhekke and van der Ploeg (2013) with the same sample in the same period. They reported that in previously non-resource countries, discovering resources led to nonresource FDI to decreasing by 16% in the short term and by 68% in the long term.…”
Section: Review Of Literaturesupporting
confidence: 54%
“…As a natural resource proxy, we employ oil rents as a share of GDP as a measure of resource dependence (Asiedu 2013;Poelhekke and van der Ploeg 2013) It is worth mentioning that a high/low Oil rents/GDP ratio indicates the high/low diversification of the country. We hypothesize a negative relationship between natural resources and aggregate FDI.…”
Section: Data Model and Methodologymentioning
confidence: 99%
“…Bohn & Deacon (2000) demonstrate that countries with undemocratic institutions and endemic conflict tend to be poor investment risks for extractive firms; hence these countries tend to have both less exploration and slower extraction rates, a finding consistently echoed by later studies (Cotet & Tsui 2013, Cust & Harding 2013, Poelhekke & van der Ploeg 2013, Metcalf & Wolfram 2014.…”
Section: What Are Natural Resources and How Are They Measured?mentioning
confidence: 77%
“…Natural resource endowment is nonsignificant, which is not surprising. Although it may foster natural resource seeking M&As, it may also deter it due to the natural resource curse on FDI (Poelhekke & van der Ploeg, ). BIT also turn to have a nonsignificant effect.…”
Section: Resultsmentioning
confidence: 99%